Bioactive Glass Reinforced Polyurethane Scaffold Effect Of Hard Segment Content Of Polyurethane - Yew, Lih Wei (Universiti Sains Malaysia, 2018)
This study emphasized on the effect of hard segment content of polyurethane (PU) on the properties of bioactive glass (BG) reinforced PU. Five types of bioactive glass (BG) reinforced PU scaffolds with 40 wt.% to 55 wt.% hard segment content of PU were fabricated by salt leaching method. PU with different hard segment contents were synthesized through two-step polymerization. Before in vitro immersion in Hank’s Balanced Salt Solution (HBSS), the fabricated scaffolds were characterized based on morphological, structural, physical and mechanical properties using field emission scanning electron microscopy (FESEM), fourier transform infrared spectroscopy (FTIR), porosity test and compression test. The scaffolds were successfully fabricated with more than 75% porosity with open pores of 110 – 400 µm which is suitable for bone tissue applications. Compressive strength of the scaffolds ranges from 0.14 MPa to 0.4 MPa. In vitro experiments were carried out to investigate the bioactivity and biodegradation of the scaffolds upon immersion in HBSS. The surface morphology and chemical properties of the scaffolds were evaluated and revealed the formation of hydroxyapatite (HA) layer onto the surface of the scaffolds. Scaffolds fabricated with the highest hard segment content showed the lowest degradation rate. The dissolution of decreased Ca and P ions product into HBSS confirmed that the BG reacted to form the HA layer.